2008
DOI: 10.1519/jsc.0b013e318173936c
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a JOURNAL/jscr/04.03/00124278-200807000-00013/OV0312_4/v/2021-02-09T093601Z/r/image-png o2 Deflection Point Coinciding With the Heart Rate Deflection Point and Ventilatory Threshold in Cycling

Abstract: The purposes of this study were to compare the patterns of the work rate (WR)-Vo2 and WR-heart rate (HR) relationships in incremental cycling, to ascertain the occurrence of a Vo2 deflection (Vo2def) coinciding with the HR deflection point (HRdef ), and to determine whether the Vo2def, if present, coincides with the ventilatory anaerobic threshold (VT). Twenty-four professional cyclists performed a maximal incremental test on a wind-load cycle ergometer. Work rate, HR, Vo2, and Vco2 were recorded. The WR-Vo2 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…Several studies in the literature have demonstrated the application of the HRDP to determine the AT in different land-based exercise modalities [10][11][12]15,[25][26][27] . However, in the aquatic environment there are, currently, few studies available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in the literature have demonstrated the application of the HRDP to determine the AT in different land-based exercise modalities [10][11][12]15,[25][26][27] . However, in the aquatic environment there are, currently, few studies available.…”
Section: Discussionmentioning
confidence: 99%
“…Also on a treadmill, Sentija et al 11 concluded that a ramp protocol can be used to determine the HRDP in trained runners. In incremental cycling, strong correlations were found between the AT, as determined by the HRDP, and the blood lactate response 12 . Mikulic et al 13 compared physiological variables and performance on a rowing ergometer between two methods of determining the AT (HRDP and VM) and found a close relationship.…”
Section: Introductionmentioning
confidence: 97%
“…A city bike was mounted on a wind-load simulator equipped with a crank set with a built-in power measuring system (SRM Training System, Jülich-Welldorf, Germany). 5 Bicycle gearing was individualized according to the functional capacity of the individual; the mean distance covered in 1 rpm was 5.49 ± 0.4 m.…”
Section: Testing Protocolmentioning
confidence: 99%
“…The evaluation of AT through the measurement of blood lactate transition thresholds is commonly performed in sports science assessment and prescription of the optimal training intensities (Fell, 2008;Grazzi et al, 2008;Wonisch et al, 2002).…”
Section: Introductionmentioning
confidence: 99%